THE APPLICATION OF IOT SOLUTIONS IN GREENHOUSES WITH THE AIM OF REDUCING ELECTRICAL ENERGY CONSUMPTION - Šaš, Milan; Pejic, Dragan (Journal on Processing and Energy in Agriculture, 2021)
In this paper, we will show a prototype of a system designed based on Internet of Things solutions with the aim of optimizing electrical energy consumption in order to achieve desired conditions for the growth and development of plants located in the greenhouse. The physical parameters that this system monitors are temperature, relative humidity, soil humidity and luminescence levels. In this prototype, we have three measurement nodes with the task of collecting parameter data, processing them and sending resulting data, via wireless communication, to a receiver. The receiver forwards data to the application on PC. The application processes the data and displays it to the end user who can choose to automatically or manually control the devices that are inside of the greenhouse. Systems placed inside the greenhouse are heating, irrigation, lighting and ventilation systems.
Keywords: prototype; greenhouse; application; Python; control